From a Society of Prowess to a Knowledge Regime - Pertierra, Raul (Kasarinlan: Philippine Journal of Third World Studies; Vol 10 No 2 (1994): Rethinking the State and the Economy 2, 2008)
Philippines 2000 is intended to transform the country into a newly industrializing country by the 21st century. Whether or not the country could thus be transformed in the immediate future is highly debatable; what is undisputedly certain, however, is that this future is crucially dependent on the steady accumulation of, and access to, knowledge. The institution of a ‘knowledge regime’ is only possible under specific scientific epistemic conditions exemplified in the contemporary Western state. Such conditions do not presently exist in the Philippines. Throughout its history, the basis of Philippine society has been in a form of personal and collective prowess ensuring protection for allies, friends or kin, and marked by a predatory orientation towards others. Contemporary conditions call for the reexamination of this basis.